Proceedings of the 2014 ACM Conference on Web Science 2014
DOI: 10.1145/2615569.2615686
|View full text |Cite
|
Sign up to set email alerts
|

"Supertagger" behavior in building folksonomies

Abstract: A folksonomy is ostensibly an information structure built up by the "wisdom of the crowds", but is the "crowd" really doing the work? Tagging is in fact a sharply skewed process in which a small minority of users generate an overwhelming majority of the annotations. Using data from the social music site Last.fm as a case study, this paper explores the implications of this tagging imbalance. Partitioning the folksonomy into two halves -one created by the prolific minority and the other by the non-prolific major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Figure 10 presents average user SPEAR expertise scores as a function of user annotation count. Consistent with our previous work (Lorince et al, 2014), we find an overall positive relationship in both Last.fm and Delicious such that average user expertise increases with number of annotations, although the data is noisy for high annotation counts. This suggests that supertaggers are not only more prolific, but also more expert, in their tagging behavior, at least as defined by SPEAR.…”
Section: Spear Expertisesupporting
confidence: 89%
See 3 more Smart Citations
“…Figure 10 presents average user SPEAR expertise scores as a function of user annotation count. Consistent with our previous work (Lorince et al, 2014), we find an overall positive relationship in both Last.fm and Delicious such that average user expertise increases with number of annotations, although the data is noisy for high annotation counts. This suggests that supertaggers are not only more prolific, but also more expert, in their tagging behavior, at least as defined by SPEAR.…”
Section: Spear Expertisesupporting
confidence: 89%
“…Many efforts have been made to infer taxonomies from folksonomies, synthesizing the advantages of controlled vocabulary and crowdsourced curation (Kubek et al, 2010;Niepert et al, 2007). Due to their low economic costs of implementation and curation, folksonomies have been implemented in diverse domains, including Flickr (photos, Nov et al, 2008;Nov and Ye, 2010), Delicious (web bookmarks, Golder and Huberman, 2006), Last.fm (music, Lorince and Todd, 2013;Lorince et al, 2014), and Bibsonomy (academic papers, Hotho et al, 2006). Reviews of many early social tagging systems can be found in Marlow et al (2006) and Sen et al (2006).…”
Section: Folksonomies: From Individual Tagging Choices To Social Contmentioning
confidence: 99%
See 2 more Smart Citations